THE IMPACT OF ENVIRONMENTAL SANITATION ON THE INCIDIENCE OF DIARRHEA IN COASTAL AREA: A LITERATUR REVIEW - Rusydi, Muh. Kemal Ikhsan; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT Until now, diarrhea is still a health problem in various parts of the world, including Indonesia. Diarrhea is a disease that can cause death for sufferers. WHO estimates there have been 4 billion cases worldwide and up to 2.2 million deaths, most of them in children under 5 years of age. Meanwhile, according to Riskesdas in 2018, diarrhea cases in Indonesia had a prevalence of 11.5%, with the highest cases being in South Kalimantan with a prevalence of diarrhea cases of 8.62% of all age groups. The purpose of this article is to study and analyze the impact of environmental sanitation on the incidence of diarrhea in coastal areas. The method used is a systematic literature review. The type of review used is mapping review. The articles used in the search were limited to the years 2019 - 2023 with the inclusion criteria being that the articles had to assess the impact of poor environmental sanitation in coastal areas by discussing diarrhea variables. In accordance with the background and objectives of the literature review from several journals analyzed, it was concluded that there is an influence between environmental sanitation and the incidence of diarrhea in coastal areas. Suggestions that can be given based on the results of the relevant literature review are the need to provide clean water for daily use as form of community prevention against environmental-based diseases such as diarrhea. Keywords: coast, diarrhea incidence, environmental sanitation